A novel colorimetric assay for α-methylacyl-CoA racemase 1A (AMACR; P504S) utilizing the elimination of 2, 4-dinitrophenolate. Issue 37 (24th March 2017) - Yevglevskis, Maksims; Lee, Guat L.; Nathubhai, Amit; Petrova, Yoana D.; James, Tony D.; Threadgill, Michael D.; Woodman, Timothy J.; Lloyd, Matthew D.
Abstract : A versatile continuous colorimetric assay for AMACR is reported. Abstract : α-Methylacyl-CoA racemase (AMACR; P504S) regulates branched-chain fatty acid degradation, activates Ibuprofen and is a recognised cancer drug target. A novel, facile colorimetric assay was developed based on elimination of 2, 4-dinitrophenolate. The assay was used to test 5 known inhibitors, determining IC50 and K i values, reversibility and characterizing irreversible inhibition.